Hak-Hak Kesehatan Reproduksi dalam Islam dan Aborsi - Faisol Rizal (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2015)
In the system quo, in terms of studies Women have always occupied a low position, limited and threatened. In this context, there is an attempt to empower women through several agencies to re-arrange the order of the spirit of global ethics, which includes the concept of justice and equality in rights and duties. With some contemporary approaches, and taking into account the conservative approach, the issue of women’s reproductive rights can be observed comprehensiveely. Conservative foothold in this case, can be considered as a material consideration in the hope footing and shooting accuracy issues that can unite goodnes solution by one of the male and female. This research resulted in the finding that women's reproductive rights are women's rights, and in its settings, especially family planning should women get the attention of her husband. In connection with the regulation of birth, can be practiced by a majority of scholars of international law and agreements. Instead, under the agreement the majority of scholars, too, the practice of abortion is prohibited. It is also supported by legislation at the practice level.